2004
DOI: 10.1128/aac.48.6.1948-1952.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ciprofloxacin, Levofloxacin, or Moxifloxacin for Treatment of Experimental Staphylococcus aureus Keratitis

Abstract: The purpose of this study was to quantitatively compare, in a rabbit keratitis model, the levels of effectiveness of moxifloxacin, levofloxacin, and ciprofloxacin for the treatment of Staphylococcus aureus isolates of diverse antibiotic susceptibilities. Rabbit eyes were intrastromally injected with approximately 100 CFU of methicillinsensitive or methicillin-resistant S. aureus (MSSA or MRSA, respectively) organisms that were either sensitive or resistant to ofloxacin. One drop of moxifloxacin (0.5%), levoflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 26 publications
1
44
0
3
Order By: Relevance
“…Levofloxacin has been used actively in ophthalmic solutions [285][286][287] for the treatment of ocular bacterial infections 288 . Bezwada et al 289 reported the intrinsic cytotoxicity of ophthalmic solutions containing levofloxacin in on human corneal keratocytes (HCK) and human corneal endothelial cells (HCE).…”
Section: It Was Discovered In 1962 and Approved By The Food Drug Admimentioning
confidence: 99%
“…Levofloxacin has been used actively in ophthalmic solutions [285][286][287] for the treatment of ocular bacterial infections 288 . Bezwada et al 289 reported the intrinsic cytotoxicity of ophthalmic solutions containing levofloxacin in on human corneal keratocytes (HCK) and human corneal endothelial cells (HCE).…”
Section: It Was Discovered In 1962 and Approved By The Food Drug Admimentioning
confidence: 99%
“…Chlorhexidine is used as antibacterial agent and topical disinfectant (Mathers, 2006), levofloxacin is an antibiotic that is widely used both in the prophylaxis and treatment of ocular infections (Dajcs et al, 2004), and diclofenac is a nonsteroidal, antiinflammatory drug with analgesic activity (Goa and Chrisp, 1992). The characteristics of the drugs are given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…5 In experimental staphylococcal keratitis model in rabbits, moxifloxacin has demonstrated greater effectiveness than ciprofloxacin or levofloxacin. 6 Experiments in rabbits suggest that surgical prophylaxis with topical 0.5% moxifloxacin could be effective for prevention of bacterial endophthalmitis. 7,8 Moxifloxacin is available as hydrochloride salt, which is water soluble.…”
Section: Introductionmentioning
confidence: 99%